PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON PADA MATERI PEMBELAJARAN GEOGRAFI DI KELAS X SMAN 1 BATIPUH - Utari, Reni Putri; Nofrion, Nofrion (JURNAL BUANA, 2023)
This study aims to determine how to design powtoon-based learning media and determine and analyze the validity and practicality of developing powtoon-based learning media on atmospheric dynamics and its impact on life. The type of research used is Research Development or Research and Development. The development model is in the form of IDI (Instructional Development Institute which has three stages, namely the definition stage, the development stage and the evaluation stage. The results of this study indicate that the percentage of validation (1) the assessment score of the material expert is 92.33 %; (2) design expert assessment of 88.53%; (3) linguistic expert assessment of 95.41%; (4) and practicality assessment by teachers of 89.69% and (5) practicality assessment by students of 89, 95%. Based on these results, the development of powtoon-based learning media is categorized as very valid and very practical so that it is feasible to use and develop. It is hoped that this application can facilitate the teaching and learning process and improve the quality of student learning achievement.